Fenología, fluctuación de poblaciones y métodos de muestreo para Thrips palmi (Thysanoptera: Thripidae) en habichuela y frijol - Osorio Cordoba, J; Cardona Mejía, César (2003)
Thrips palmi Karny is a relatively new pest of beans and snap beans in Colombia. Since its introduction to Colombia in 1997, this insect has caused severe economic losses in these crops in the Cauca Valley. Four field triáis, aimed at finding distribution patterns within the plant, oviposition sites, and damage caused by actives insect stages were conducted in Pradera, Cauca Valley (980 masl, 23°C). The information was also used to develop sampling methods. On snap beans and dry beans, adults colonize the crop, ovipositing on newly developed leaves (cotyledons at the beginning of crop development). Adults relocate within the plant searching for new tissues. Fifteen - eigteen days after colonization, first instar larvae are observed on those leaves in which oviposition occurred. Adults are found on the upper surface of leaves where they cause discoloration of leaf tissues along leaf veins. Larvae feed on the undersurface of leaves and cause bronzing of tissues. On beans, adults prefer to feed on tender leaves throughout the crop cycie. Adult and larvae of T. palmi are found aggregated on both crops. Ideal sampling size is 40 leaflets per ha taken at random from the uppermost part of plants. No differences were found when several sampling patterns were compared. A sequential sampling plan for adults (based on an action threshold of 7 adults per leaflet) was developed.